Gestión integral del costo en la fabricación de mallas industriales de la empresa Fabrimallas S.A.S del municipio de Palmira. - Ramirez Ramirez, Jazmin; Ortiz Dorado, Eliana Vanessa (Universidad Antonio Nariño, 2024)
In th ecurrent business landscape, efficient cost management stands as an essential pillar for the sustainability and success of organizations.The authors propose acomprehensive projectto Fabrimallas de PalmiraS.A.S aimed at optimizing production and meticulously controlling costs in the manufacturing of industrial meshes.